Bis(2-ethylhexyl)amine as an Effective Organocatalyst for the Racemic Reactions of α,β-Unsaturated Aldehydes Involving an Iminium Ion - Hayashi, Yujiro; Han, Xiaolei; Mori, Naoki (Synlett, 2023)
Bis(2-ethylhexyl)amine is shown to be a suitable organocatalyst to prepare racemic compounds in the reactions of α,β-unsaturated aldehydes involving an iminium ion, whereas diphenylprolinol silyl ether is a well-known chiral organocatalyst for the asymmetric versions of the same reactions. The generality and limitations of bis(2-ethylhexyl)amine are disclosed.
Keywords: organocatalysis; racemate; diphenylprolinol silyl ether; bis(2-ethylhexyl)amine; α,β-unsaturated aldehyde; iminium ion